The histone demethylase PHF8 facilitates alternative splicing of the histocompatibility antigen HLA‐G. Issue 5 (27th February 2019) - Leisegang, Matthias S.; Gu, Lunda; Preussner, Jens; Günther, Stefan; Hitzel, Juliane; Ratiu, Corina; Weigert, Andreas; Chen, Wei; Schwarz, Eva C.; Looso, Mario; Fork, Christian; Brandes, Ralf P.
Abstract : Histone3‐lysine9 (H3K9) residues not only control gene expression, but also contribute to RNA splicing. Here, the H3K9 histone demethylase PHF8 was investigated in endothelial cells for its involvement in alternative splicing. An angiogenic sprouting assay shows the importance of PHF8 for endothelial cells. Immunoprecipitation reveals that PHF8 interacts with U1 spliceosomal proteins, such as SRPK1 and snRNP70. We identify the histocompatibility antigen HLA‐G as a target of PHF8. The inclusion of HLA‐G intron 4, with concomitant RNA Polymerase II accumulation at this intron is controlled by PHF8 and H3K9. Soluble HLA‐G is generated after PHF8 knockdown, which leads to reduced T‐cell proliferation. Collectively, PHF8 knockdown generates the immunosuppressive alternative splice product soluble HLA‐G, which is secreted by endothelial cells to elicit a potential inhibitory effect on inflammation. Abstract :